Do Commercial Banks’ Non-Performing Loans Respond to Environmental Financial and Economic Influences in the Sub-Saharan Region of Africa - Asemota, Georgina; Erhi, Moses; Ihensekhien, Orobosa (Acta Universitatis Danubius. Œconomica, 2023)
Recent trends in the global economy amplify the need for financial reforms in fragile economies prevalent in the sub-Saharan region of Africa. The study aims at assessing the internal and external environmental influences on the non-performing loans of the banking sub-sector in the region. Extant studies focus primarily on either macroeconomic determinants or bank-related determinants. This work draws its pool of regressors from a wider scope and confirms its results by using multiple estimation techniques. Annual data for the period 2012 to 2021 were sourced from secondary databases for variables representing bank operations, bank quality, monetary policy, and macroeconomic conditions. Three estimation techniques- Dynamic Generalized Method of Moments (GMM), System GMM (SYS-GMM), and System Seemingly Unsure Regression (SYS-SUR)-were employed to analyze the data. The results confirm that bank quality, monetary policy and bank operations are significant determinants of non-performing loans in the region. The findings imply that the often favored policy of restricting money supply increases the incidence of non-performing loans in Sub-Saharan Africa. The study exposes the superior nature of interest rates or required reserve ratio over money supply as a monetary policy tool because of their neutral impact on non-performing loans.